Unprotected and Unparticipation Mental Health in Regulation Worker - I Wayan Gde Wiryawan; Gede Agung Wirawan Nusantara; I Wayan Eka Artajaya; Rizozoda Tura Rabbim (BESTUUR, 2024)
Unprotected mental health among employees can have a detrimental effect on productivity and the national economy. Nevertheless, Indonesia's present labor regulations do not include any specific provisions to safeguard workers' mental health. This research aims to identify and analyze issues regarding mental health workers that are often ignored, which cause decreased productivity and negative stigma for people experiencing mental health to medical personnel and facilities that are less qualified in protecting workers. This normative research examines legal texts, mainly primary and secondary legal materials. The results of the research show that, first, mental health problems in Indonesia are very complex, starting from the negative stigma that is still embedded in society regarding mental health diagnoses to regulations and law enforcement that do not support workers with mental health to recover from their illnesses. Second, based on Singapore, Singapore has a program and legal framework that supports public health and workers who experience mental health disorders monitoring that has been integrated with the system. Third, to overcome mental health problems for workers, there needs to be a clear regulatory framework that targets improving mental health, an integrated health monitoring system that is expanded to provide training for medical personnel, and health care quality.